Adipocytokines and Inflammation in Patients and a Gerbil Model: Implications for Obesity-Related and Nonobese Diabetes - Hongjuan Fang; Xiaohong Li; Jianyi Lv; Xueyun Huo; Meng Guo; Xin Liu; Changlong Li; Zhenwen Chen; Xiaoyan Du (Journal of Diabetes Research)
Conclusions: Our study, which may be considered a pilot investigation, suggests that the interaction of adipocytokines and inflammation factors in different adipose depots could play diverse roles in the development of diabetes or obesity.